Hats Off to Self‐Organisation and Self‐Assembly!. Issue 2 (September 2016) - Herz, Andreas; Wang, Dong; Schaaf, Peter
Abstract: Metallic films of nanometer thickness are used for electronic applications in which they must be stable and not decompose into nanoparticles. On the other hand, nano‐sized metallic spheres of uniform size in a defined arrangement are very interesting for new applications in optics, sensor technology and medicine. Researchers are looking to nature for help in fabricating such complicated nanomaterials. The magic word is "dewetting", a process that could enable their easy fabrication.